Dwaj ludzie z szafą w perspektywie genologicznej - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Parabola is the essence of the short film Two Men and a Wardrobe (and likewise Mammals and The Fat and the Lean). Parabola is dominant of the genre, not merely an occasional and distinguishing attribute. In its interior, we find traces of other genres. These include noir comedy, slapstick burlesque, existential drama, the thriller, and drama of the absurd, grotesque and macabre. The poetic dimension of Polanski’s short film, in which reality confronts and permeates the skilfully constructed and captivating fantasy presented by the artist, allowing all the elements of the genre to be combined into a common whole.